2018
DOI: 10.1080/10826084.2017.1408650
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drug Monitoring Programs and Pharmacist Orientation Toward Dispensing Controlled Substances

Abstract: Ongoing tracking of pharmacists' use of PDMPs is important both at the implementation stage and as PDMPs develop over time. The orientation construct developed here is useful in understanding pharmacist behavior and attitudes towards patients potentially at risk for misuse of controlled substance medications. Further research on this construct could shed light on barriers and incentives for pharmacist PDMP participation and use and provide guidance for pharmacist training, ultimately enhancing patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Attitudes and practice strategies of pharmacists towards drug misuse management and the relevance of years of practice experience were discussed in seven studies . The majority of pharmacists recruited by Leong et al and Patel et al had greater than 10 years pharmacy practice experience, and 50% of the respondents interviewed by Fendrich et al had greater than 20 years practice experience. Butler and Sheridan reported that community pharmacists with greater practice experience were more willing to confront patients about drug misuse.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Attitudes and practice strategies of pharmacists towards drug misuse management and the relevance of years of practice experience were discussed in seven studies . The majority of pharmacists recruited by Leong et al and Patel et al had greater than 10 years pharmacy practice experience, and 50% of the respondents interviewed by Fendrich et al had greater than 20 years practice experience. Butler and Sheridan reported that community pharmacists with greater practice experience were more willing to confront patients about drug misuse.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen articles reported that pharmacists felt they had gaps in knowledge related to addiction and pain management, or in the misuse potential of over‐the‐counter and opioid medications . Pharmacists in a qualitative study by Hagemeier et al, that specifically explored pharmacists' perceptions of the behaviours of patients who were misusing drugs and the associated challenges reported that they felt they lacked the knowledge to deal with aggressive and intimidating patient behaviour .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations